The Modern Primitives: Applying New Technological Approaches to Explore the Biology of the Earliest Red Blood Cells. (3rd October 2013) - Fraser, Stuart T.
Abstract : One of the most critical stages in mammalian embryogenesis is the independent production of the embryo's own circulating, functional red blood cells. Correspondingly, erythrocytes are the first cell type to become functionally mature during embryogenesis. Failure to achieve this invariably leads to in utero lethality. The recent application of technologies such as transcriptome analysis, flow cytometry, mutant embryo analysis, and transgenic fluorescent gene expression reporter systems has shed new light on the distinct erythroid lineages that arise early in development. Here, I will describe the similarities and differences between the distinct erythroid populations that must form for the embryo to survive. While much of the focus of this review will be the poorly understood primitive erythroid lineage, a discussion of other erythroid and hematopoietic lineages, as well as the cell types making up the different niches that give rise to these lineages, is essential for presenting an appropriate developmental context of these cells.